The Role of Military Diplomacy in Nepal’s Foreign Policy - Paudel, Jiwan (Unity Journal, 2022)
Military diplomacy is the exploitation of a range of military resources, both bilaterally and multilaterally, to create favorable and cooperative ties with foreign nations in a pacific manner. Mutual security pacts, defense assistance, intelligence sharing, anti-piracy missions, joint military drills, communications assistance, disaster-relief missions, and high-level engagements between senior military hierarchies comprise military diplomacy. Military diplomacy aims to fill in the gaps, when needed, to help its parent nation respond to the challenges and complexity of disruptive, fast changing, strife-torn geopolitical circumstances while working in tandem with other state instruments. Nepal Army’s intense experiences in jungle and mountain warfare’s, tactical operations, and its redoubtable military training exercises have been employed to develop vibrant bilateral relations. The compelling military diplomacy of Nepal Army with foreign nations led to unstinting support and assistance in garnering essentials during the devastating earthquake and COVID-19 situation. Peacekeeping force should be prioritized to enhance foreign policy and seek to direct Foreign Direct Investment to Nepal. Appointment of military attaché to the nations having bilateral relations with Nepal, hosting of cultural and sports meet, high altitude training etc. would strengthen bilateral military relation along with improved foreign policies. The first part of this paper explores the role of Nepalese military diplomacy in Nepal’s foreign policy with Britain, India, China and United Nation in various time periods followed by second part focusing on SWOT analysis, possible counsels for better diplomacy and future prospects. This paper is framed with doctrinal methodology wherein primary data were collected from statues, seminar brochures, research and review papers, interview of current and ex-Nepal Army officer and Ministry of defense reports whereas secondary data sources used for the study are legal prodigals, treaties, encyclopedia, newspaper, reports, and bona fide information